Perioperative management of patients recovered/recovering from COVID-19 infection with mucormycosis: A case series with practical recommendations (Panacea Journal of Medical Sciences, 2024)
Mucormycosis as a secondary fungal invasion in COVID-19 patients has been described in individual reports worldwide. However, India has declared mucormycosis epidemic in four states and one union territory. The sudden plethora of rhino-orbital mucormycosis cases in India has put the medical faculty to ponder over etiology behind such peaking graph of cases while braving it out trying to save these patients. As anaesthesiologists, the peri-operative management of these cases is a challenge due to known usual and unusual as well as yet unknown long-term multi-system derangements found in COVID-19 illness in addition to the serious nature of this aggressive fungal invasion. We are presenting a case series of six patients who underwent Functional Endoscopic Sinus Surgery along with orbital exenteration for mucormycosis. Key Messages: Peri-operative management of mucormycosis in COVID-19 patients requires multidisciplinary evaluations, cardio-pulmonary optimisation and tight blood sugar control for better outcome. The ulterior goal should be avoiding exacerbation of post-COVID sequalae as well as extensive debridements along with Amphotericin b therapy to prevent further mocormycosis invasion.